Palm tocotrienol-rich fraction reduced plasma homocysteine and heart oxidative stress in rats fed with a high-methionine diet - Ku Zaifah, Norsidah; Asmadi, Ahmad Yusof; Azizi, Ayob; Othman, Faizah; Kamisah, Yusof (Springer Netherlands, 2013)
Oxidative stress contributes to cardiovascular diseases. We aimed to study the effects of palm tocotrienol-rich fraction (TRF) on plasma homocysteine and cardiac oxidative stress in rats fed with a high-methionine diet. Forty-two male Wistar rats were divided into six groups. The first group was the control. Groups 2-6 were fed 1 % methionine diet for 10 weeks. From week 6 onward, folate (8 mg/kg diet) or palm TRF (30, 60 and 150 mg/kg diet) was added into the diet of groups 3, 4, 5 and 6. The rats were then killed. Palm TRF at 150 mg/kg and folate supplementation prevented the increase in plasma total homocysteine (4.14 ± 0.33 and 4.30 ± 0.26 vs 5.49 ± 0.25 mmol/L, p < 0.05) induced by a high-methionine diet. The increased heart thiobarbituric acid reactive substance in rats fed with high-methionine diet was also prevented by the supplementations of palm TRF (60 and 150 mg/kg) and folate. The high-methionine group had a lower glutathione peroxidase activity (49 ± 3 vs 69 ± 4 pmol/mg protein/min) than the control group. This reduction was reversed by palm TRF at 60 and 150 mg/kg diet (p < 0.05), but not by folate. Catalase and superoxide dismutase activities were unaffected by both methionine and vitamin supplementations. In conclusion, palm TRF was comparable to folate in reducing high-methionine diet-induced hyperhomocysteinemia and oxidative stress in the rats' hearts. However, palm TRF was more effective than folate in preserving the heart glutathione peroxidase enzyme activity.